Characteristics of the semantic content of the concept of "game giftedness" (using the example of football) - Rizvanova A.A. , (Theory and Practice of Physical Culture, 2025)
Abstract Objective of the study – to scientifically substantiate the essence and content of the concept of “gaming talent” in sports activities. Methods and structure of the study. To achieve the goal, a study was conducted using the following methods: analysis of scientific and methodological literature (using the ResearchGate, Google Scholar and PubMed databases). Results and conclusions. Gaming talent is an original systemically developing model of readiness for gaming activity, expressed in the totality and qualitative uniqueness of innate physical (speed of action), psychophysiological (perception, sensorimotor reactions, gaming intelligence) and acquired social (propensity for gaming interaction, emotional and social intelligence) qualities, which make it possible to compensate for the insufficiency of some functional qualities due to the priority of the evolution of others. The content of gaming talent consists of physical, psychophysiological and social qualities.